The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3386/w25080
|View full text |Cite
|
Sign up to set email alerts
|

Vanished Classmates: The Effects of Local Immigration Enforcement on Student Enrollment

Abstract: NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…24 Since 287(g) agreements took place before DACA (Watson, 2013), that policy is less likely to contaminate our effects, and we find no evidence of significant responses in our pre-trend analysis. Furthermore, Dee and Murphy (2018) find that 287(g) actually reduced high school enrollment, which implies that contamination from this program are likely to imply that our estimates are conservative. The Criminal Alien Program (CAP) also saw expansions many years prior to DACA.…”
Section: Robustnessmentioning
confidence: 89%
“…24 Since 287(g) agreements took place before DACA (Watson, 2013), that policy is less likely to contaminate our effects, and we find no evidence of significant responses in our pre-trend analysis. Furthermore, Dee and Murphy (2018) find that 287(g) actually reduced high school enrollment, which implies that contamination from this program are likely to imply that our estimates are conservative. The Criminal Alien Program (CAP) also saw expansions many years prior to DACA.…”
Section: Robustnessmentioning
confidence: 89%
“…However, even in the face of falling achievement for individual children, immigration enforcement policies may increase measured average achievement by Hispanic students if newly implemented immigration enforcement policies lead to families with unauthorized members migrating or withdrawing children from school. Following increases in immigration enforcement, children of unauthorized immigrants are more likely to leave school (Amuedo-Dorantes & Lopez, 2015) and the activation of a different type of partnership between ICE and local law enforcement, 287(g) programs, decreased Hispanic enrollment in affected counties (Dee & Murphy, 2018). Considering that the children of unauthorized parents likely perform below other Hispanic children, in part because they belong to a more vulnerable, lower income population, removing them from the school system may increase the average levels of performance for Hispanic students.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…They find that effects are concentrated primarily among younger students, with the children of likely unauthorized immigrants aged 6 to 13 years more likely to repeat grades and drop out of school in the wake of immigration enforcement policies. The activation of 287(g) programs specifically decreased the school enrollment of Hispanic students (Dee & Murphy, 2018), although it is unclear whether this decrease is the result of migration or dropping out.…”
Section: Prior Researchmentioning
confidence: 99%
“…Sanctuary policies have received heightened attention and scrutiny from policymakers, primarily driven by concerns over public safety related to increased undocumented immigration. Apart from the empirical research not supporting a link between sanctuary policy adoption and crime, other research has found negative effects of increased immigration enforcement on education more broadly (Amuedo-Dorantes & Lopez, 2017;Bellows, 2019;Dee & Murphy, 2019). Immigrant youth, who already face uncertain futures due the intersection of their undocumented status and federal law, may also bear some of the biggest burden of immigration enforcement, leading them to miss school or transfer school districts (Dee & Murphy, 2019).…”
Section: Discussionmentioning
confidence: 99%